Diurnal variability of glucose tetrasaccharide (Glc4) excretion in patients with glycogen storage disease type III. Issue 1 (3rd November 2020) - Young, Sarah P.; Khan, Aleena; Stefanescu, Ela; Seifts, Andrea M.; Hijazi, Ghada; Austin, Stephanie; Kishnani, Priya S.
Abstract: Aim: The urinary glucose tetrasaccharide, Glcα1‐6Glcα1‐4Glcα1‐4Glc (Glc4 ), is a glycogen limit dextrin that is elevated in patients with glycogen storage disease (GSD) type III. We evaluated the potential of uncooked cornstarch therapy to interfere with Glc4 monitoring, by measuring the diurnal variability of Glc4 excretion in patients with GSD III. Methods: Voids were collected at home over 24 hours, stored at 4°C and frozen within 48 hours. Glc4 was analyzed using liquid chromatography‐tandem mass spectrometry and normalized to creatinine. Results: Subjects with GSD III (median age: 13.5 years, range: 3.7‐62; n = 18) completed one or more 24‐hour urine collection, and 28/36 collections were accepted for analysis. Glc4 was elevated in 16/18 subjects (median: 13 mmol/mol creatinine, range: 2‐75, reference range: <3). In collections with elevated Glc4 (23/28), two‐thirds (15/23) had low diurnal variability in Glc4 excretion (coefficient of variation [CV%] <25). The diurnal variability was significantly correlated with the Glc4 concentration (Pearson R = .644, P < .05), but not with the dose of uncooked cornstarch. High intraday variability (>25%) was not consistently observed in repeat collections by the same subject. Conclusions: The extent and variability of Glc4 excretion relative to creatinine was not correlated with cornstarch dose. A majority of collections showed low variability over 24 hours. These findings support the use of single time‐point collections to evaluate Glc4 in patients with GSD III treated with cornstarch. However, repeat sampling over short time‐periods will provide the most accurate assessment of Glc4 excretion, as intraday variability may be increased in patients with high Glc4 excretion.